Business marketing : Connecting strategy, relationships, and learning - Dwyer, F. Robert (McGraw-Hill/Iwin, 2006)
This text is targeted at the undergraduate Business Marketing course. It introduces the concepts of marketing to businesses and stresses the importance of building relationships with customers.